Retrospective Single-Center Study on Patency and Clinical Outcomes of Transjugular Intrahepatic Portosystemic Shunt Placement Using Niti-S Stents in Patients with Cirrhosis - Sasidharan, Rajesh; Suryavanshi, Shubham; Baby, Akhil; Philips, Cyriac Abby; Oommen, Tharun Tom; Tharakan, Ajit (Journal of Clinical Interventional Radiology ISVIR, 2025)
To evaluate the primary patency rates and clinical outcomes of the Niti-S expanded polytetrafluoroethylene-covered stent when used for transjugular intrahepatic portosystemic shunt (TIPS) creation in cirrhotic patients, and to compare outcomes with published Viatorr benchmarks.This retrospective single-center study included 96 cirrhotic patients who underwent de novo TIPS placement using Niti-S ComVi biliary (end bare-type) stents between April 2021 and March 2024. Indications included variceal bleeding (54%) and recurrent or refractory ascites (46%). TIPS creation followed a standardized protocol, and patients were prospectively followed with Doppler ultrasound and clinical assessment. The primary endpoint was 12-month primary patency, defined as uninterrupted stent function without re-intervention.Hemodynamic success was 100%, with significant reduction in portal pressure gradient (from 23  ±  5 to 9  ±  4 mmHg). Primary patency rates at 6 months, 1 year, and 2 years were 97, 96, and 92%, respectively. There was no significant difference in patency by TIPS indication. At 1 year, clinical outcomes demonstrated a 96% rate of freedom from rebleeding and complete resolution of ascites in 91% of patients. After a median follow-up of 20 months, 12.5% patients developed hepatic encephalopathy, including 3.2% with episodes of West Haven grade III–IV severity. Comparative analysis revealed that the patency rates and clinical outcomes of the Niti-S stent were on par with those reported for Viatorr.The Niti-S covered stent demonstrated excellent 1-year patency and clinical efficacy in TIPS creation. It offers a viable alternative in resource-limited settings, with effective portal decompression and low complication rates.
Keywords: variceal bleeding; encephalopathy; ascites